Glenohumeral joint rotation range of motion in competitive swimmers - Riemann, B. L.; Witt, J.; Davies, G. J. (Journal of Sports Sciences, 2011)
Much research has examined shoulder range of motion adaptations in overhead-unilateral athletes. Based on the void examining overhead-bilateral athletes, especially competitive swimmers, we examined shoulder external rotation, isolated internal rotation, composite internal rotation, and total arc of motion range of motion of competitive swimmers. The range of motion of registered competitive swimmers (n = 144, age = 12-61 years) was compared by limb (dominant, non-dominant), sex, and age group (youth, high school, college, masters). Significantly (P < 0.05) greater dominant external rotation was observed for both men and women high school and college swimmers, youth women swimmers, and men masters swimmers compared with the non-dominant limb. The isolated internal rotation (glenohumeral rotation), composite internal rotation (glenohumeral rotation plus scapulothoracic protraction), and total arc of motion (external rotation plus composite internal rotation) of the non-dominant limb was significantly greater than that of the dominant limb by sex and age group. Youth and high school swimmers demonstrated significantly greater composite internal rotation than college and masters swimmers. Youth swimmers displayed significantly greater total arc of motion than all other age groups. These data will aid in the interpretation of shoulder range of motion values in competitive swimmers during preseason screenings, injury evaluations and post-rehabilitation programmes, with the results suggesting that differences exist in bilateral external rotation, isolated internal rotation, composite internal rotation, and total arc of motion range of motion.